INTERNAL NEGATIVE INFORMATION-PSYCHOLOGICAL INFLUENCES IN UKRAINE: REGULATION OF THE ACTIVITY IN INFORMATION SPACE AS MEANS OF LEVELING - Конах, В.К. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
In the article are determined the current trends of using the internal negative information-psychological influences, the main factors that contribute to high levels of ttheir performance, based on the analysis of the national information space of Ukrain. Proposed areas of regulation of the activity in the information space, with a view to their leveling.